2015
DOI: 10.1155/2015/942147
|View full text |Cite
|
Sign up to set email alerts
|

Gadolinium(III) Complexes with N-Alkyl-N-methylglucamine Surfactants Incorporated into Liposomes as Potential MRI Contrast Agents

Abstract: Complexes of gadolinium(III) with N-octanoyl-N-methylglucamine (L8) and N-decanoyl-N-methylglucamine (L10) with 1 : 2 stoichiometry were synthesized and characterized by elemental analysis, electrospray ionization-tandem mass spectrometry (ESI-MS), infrared (IR) spectroscopy, and molar conductivity measurements. The transverse (r 2) and longitudinal (r 1) relaxivity protons were measured at 20 MHz and compared with those of the commercial contrasts. These complexes were incorporated in liposomes, resulting in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Metal chelates can also be decorated onto the surface of liposome- or micelle-based NPs, and the resulting NPs afford r 1 as high as 134.8 mM -1 s -1 at 3.0 T due to prolonged rotational correlation times 84 - 86 . For instance, the Botta group developed a Gd(DOTA)-grafted lipid NP by modifying Gd(DOTA) with two carbon-chain anchors (i.e., GAC 12 ) and inserting them into the lipid bilayer ( Figure 3 A ) 87 .…”
Section: Nanoparticle or Macromolecule Contrast Agents With Enhanced mentioning
confidence: 99%
“…Metal chelates can also be decorated onto the surface of liposome- or micelle-based NPs, and the resulting NPs afford r 1 as high as 134.8 mM -1 s -1 at 3.0 T due to prolonged rotational correlation times 84 - 86 . For instance, the Botta group developed a Gd(DOTA)-grafted lipid NP by modifying Gd(DOTA) with two carbon-chain anchors (i.e., GAC 12 ) and inserting them into the lipid bilayer ( Figure 3 A ) 87 .…”
Section: Nanoparticle or Macromolecule Contrast Agents With Enhanced mentioning
confidence: 99%
“…It was demonstrated that the relaxivity of a dendrimer's Gd chelate is related to its mobility and that a high relaxivity rate is generally induced by a low mobility. High relaxivity can also be achieved by conjugation with macromolecules such as virus capsids [19, 20], nanoparticles [21], and liposomes [22, 23]. Manus et al prepared a Gd(III)-nanodiamond conjugate [Gd(III)-ND] with three Gd-chelate molecules.…”
Section: Introductionmentioning
confidence: 99%